2017
DOI: 10.1039/c7cc02911j
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule conductance of DNA gated and ungated by DNA-binding molecules

Abstract: The single-molecule conductance of DNA was found to increase by over four fold upon intercalation, while the conductance nearly unaltered upon groove-binding. These effects are interpreted on the basis of the electronic interaction of the DNA-binding molecules with the stacked DNA bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…To this end, a technique based on scanning tunneling microscopy (STM) has been widely employed to investigate the electron transport in a single molecule . A variety of functional molecules such as diodes, switches, and transistors are being developed through such transport measurement. For example, it was found that conductance switching can be achieved by a photochromic reaction using diarylethene .…”
Section: Figurementioning
confidence: 99%
“…To this end, a technique based on scanning tunneling microscopy (STM) has been widely employed to investigate the electron transport in a single molecule . A variety of functional molecules such as diodes, switches, and transistors are being developed through such transport measurement. For example, it was found that conductance switching can be achieved by a photochromic reaction using diarylethene .…”
Section: Figurementioning
confidence: 99%
“…2015 年, Bruot 等 [51] [51] Figure 2 (a) A typical current-distance trace recorded in experiment. The plateau indicates a stable molecular junction was established between the tip and substrate; (b) Schematic of the modified STM-BJ setup with a modulating tip; (c) The evolution of amplitude of conductance modulation with time as the junction was mechanically modulated [51] 2017 年, Harashima 等 [52] 基于 STM-BJ 技术, 发现了 通过调控碱基对之间的 π-π 堆积作用, 可以实现对 DNA 分子的电导调控. 如图 3a 所示, 研究者采用了溴化乙锭 (ethidium bromide, EB)和 Hoechst 33258 (HOE)两种染料 分子.…”
Section: 扫描隧道显微镜裂结法mentioning
confidence: 99%
“…图 3 (a) EB 分子和 HOE 分子的结构式, 以及其与 DNA 分子结合位 点的示意图; (b) 与 EB 分子发生结合后, 实验中测得的 DNA 分子的 一维电导统计柱状图; (c) 与 HOE 分子发生结合后, 实验中测得的 DNA 分子的一维电导统计柱状图 [52] Figure 3 (a) Chemical structures of EB and HOE molecules, and the schematic illustration of the formation of EB-DNA complex and HOE-DNA complex; (b) 1D conductance histogram and typical traces for EB-DNA molecular junction; (c) 1D conductance histogram and typical traces for HOE-DNA molecular junction [52] 电化学方法具有调控分子能级的能力, 并且与其他 调控方法相比, 电化学具有经济、 方便、 高效等优势. 一 般情况下仅需要施加数百毫伏的电压, 即可以显著地改 变反应的势垒、方向和产物.…”
Section: 扫描隧道显微镜裂结法unclassified
“…[1] To this end, at echnique based on scanning tunneling microscopy (STM) has been widely employed to investigate the electron transport in as ingle molecule. [2][3][4][5] Av ariety of functional molecules such as diodes, [6][7][8][9] switches, [10][11][12][13] and transistors [14][15][16][17] are being developed through such transport measurement. Fore xample,i tw as found that conductance switching can be achieved by ap hotochromic reaction using diarylethene.…”
mentioning
confidence: 99%